Greenhouse Gas Emissions From Tropical Peat Forest And Peat Oil Palm Plantation - A Review - Chieng, B.Y (Universiti Malaysia Sarawak , (UNIMAS), 2009)
Reviews had been carried out on related journals in determining the GHG emissions from tropical peatlands and peat oil palm plantations. Majorities of GHG are CH2, CH4 and N2O, with CO2 consisted of 90% of total GWP while CH4 and N2O contributed <1% of total GWP.